Peningkatan Kemampuan Interpretasi Grafik Peserta Didik melalui Aplikasi Physics Toolbox Sensor Suite pada Pembelajaran Gerak Harmonik Sederhana - Lutfia Maulidina; Wayan Suana; Chandra Ertikanto (Universitas Nurul Huda, 2024)
This study aims to describe the effectiveness of practicum activities assisted by the Physics Toolbox Sensor Suite (PTSS) application with the discovery learning model in improving students' graph interpretation skills. The research employed an experimental method with a nonequivalent control group design and was conducted at SMA S Global Madani Bandar Lampung. The instrument used was an essay test on pendulum and spring subtopics. The results showed that the N-gain of the experimental class was in the high category (0.71), while the control class was in the medium category (0.50). The Mann-Whitney hypothesis test produced a significant value (0.001 < 0.05), indicating a difference in the average improvement of graph interpretation skills between the two classes. Furthermore, the effect size test yielded a d'Cohen value of 0.841, categorized as high. These findings suggest that practicum activities based on discovery learning with the PTSS application significantly enhance students' graph interpretation skills compared to manual practicum activities.